Własność jako prawo zabezpieczające w Polsce w okresie od 1946 do 1990 roku - Gołaczyński, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
An interesting issue related to the ownership right is whether it can fulfill the function of securing the realization of receivables. The point is to determine whether the ownership right may constitute a law securing compulsory payment of a debt, similarly to pledge rights (pledge, mortgage). This issue was the subject of practice already under the rule of property law of 1946 and the Civil Code of 1964 that is, throughout the period of the socialist economy. Regulation of property rights in the Constitution of the People’s Republic of Poland of 1952 and the Civil Code of 1964 was diversified due to the introduction of types of ownership (state, cooperative, individual and personal). Hence the important question whether property rights could be used as a security right at all times, or only with respect to individual or personal property? The property was used to secure credit and loans. Owing to the resolution of the Supreme Court of May 10, 1948, in the absence of an effective lien, the property became a legal means to secure the loan, similar to the German Sicherungsuebereignung. Such a function was fulfilled by the property right in the security transfer of property, both under the decree on property law of 1946 and under the Civil Code of 1964. Despite this, there was still a discussion about the admissibility of using the seizure of property taken over from German law, especially with regard to real estate. The prevailing view was that the collateral transfer could not be applied to state and cooperative property. The banks that granted loans at that time were state-owned or cooperative entities. The loan was granted by a state-owned bank to a state legal person, which was related to the theory of uniform state ownership, nationwide ownership, or state ownership.
Keywords: prawo własności; przewłaszczenie na zabezpieczenie; zastrzeżenia prawa własności